The potential of ecological corridors for resilient cities in São Paulo and Mogi das Cruzes - Sandeville Jr. , Euler Sandeville Jr.; Ijano, Valdirene (Technical and Scientific Journal Green Cities, 2025)
Objective – Analyze the connectivity potential of ecological corridors based on the improvement of urban planning instruments and interpretation of the environmental and urban dynamics of the cities of São Paulo and Mogi das Cruzes. The aim is to identify possibilities and difficulties for the preservation and expansion of the remaining Atlantic Forest in terms of its potential to reconfigure urban environmental structures in the context of each of these cities. Methodology – This research is based on mapping and theoretical references related to the topic in question, analyzing the potential of vegetation in the existing urban environmental structure, the possibilities for reducing the fragmentation of native vegetation, protected areas, and urbanized areas. With this, we point to a necessary discussion of provisions set forth in the Master Plans and Municipal Plans for the Atlantic Forest of each municipality in view of a possible urban environmental structure as a constraint on landscape planning, identifying some advances and difficulties that persist. Originality/Relevance – Analyze the connectivity of forest fragments with their surroundings, observing configurations and dynamics on a regional scale. Results –This study highlights some structural weaknesses and potentialities of these municipalities in terms of ecological connectivity and points to possible planning actions aimed at an environmental urban structure, considering the preservation of fragments and expansion of green areas. Theoretical/Methodological Contributions – To spark new discussions on the possibilities of reconfiguring urban environmental structures in the context of each of these cities, seeking a point of convergence between environmental and social issues based on collective participation by the population. Social and Environmental Contributions – Improvement of sustainable development strategies for resilient cities, considering short to long term measures, with a view to urban and environmental planning and the necessary mitigation and adaptation actions in the face of climate change.